PRESERVING OF TRADITIONAL ARTS THROUGH RANDAI TRAINING IN NAGARI SUNGAI LANDIA - Susanti, Desi; Wenhendri, Wenhendri (Batoboh, 2019)
Some Minangkabau traditional arts can live and develop in accordance with the times, but on the other hand some others  have no more supporting communities and  will just disappear in time. The same thing also happened in Nagari Sungai Landia, District IV Koto Agam Regency, West Sumatra. Nagari or this village is on the Padang Lua-Maninjau route or a road that connects Bukittinggi and Maninjau. Randai training as an effort to preserve traditional art to the young generation in Nagari Sungai Landia with the aim to bring the Minangkabau traditional art closer to the younger generation or millennial generation, so that the wealth of this unique Minangkabau art will be maintained among global developments that are increasingly distancing the young generation in their environment. The development and training of randai uses lecture and practice methods, so that after the training ends, the community or young generation is expected to be able to master good randai play techniques so that they can compete at the local level.